Mennonite valley girl : a wayward coming of age - Funk, Carla, 1974- (Greystone Books, 2021)
"A funny and whip-smart memoir about a feisty young woman's quest for independence in an isolated Mennonite community. Carla Funk is a teenager with her hands on the church piano keys and her feet edging ever closer to the flames. Coming of age in a remote and forested valley--a place rich in Mennonites, loggers, and dutiful wives who submit to their husbands--she knows her destiny is to marry, have babies, and join the church ladies' sewing circle. But she feels an increasing urge to push the limits of her religion and the small town that cannot contain her desires for much longer. -Teenage (Mennonite) angst at its finest: Carla questions the patriarchal norms of Mennonite society and yearns to break free. She'll start by lighting her driveway on fire .... -A family story: the perfect gift for mothers, daughters, sisters, and fathers and sons. -Pitch-perfect 1980s nostalgia: remember Jordache jeans? -For readers of Miriam Toews: heart wrenching and humorous descriptions of Mennonite life. At once a coming-of-age story, a contemplation on meaning, morality, and destiny, and a hilarious time capsule of 1980s adolescence, Mennonite Valley Girl offers the best kind of escapist reading for anyone who loves small towns, or who was lucky enough to grow up in one."--